Encouraging Classroom Learning through Game-Based Learning (GBL) Approach - Othman Ali, Nur Hanis; JAMIAN, RAHIM; YASAK, MOHD FUAD (Progress in Engineering Application and Technology, 2021)
In recent years, gamification of learning through student-centred approach (SCA) is getting more attention from educators to encourage student participation than conventional method in teaching and learning (T&L) process. Nonetheless, the nature of hazards and incident risk in several university courses and training sessions in the industry including occupational safety course constrains the implementation of SCA in real-life situation as it may bring harm to human and the environment. Thus, this research was attempted to investigate the effect of game-based learning (GBL) approach on student participation and achievement in occupational safety course. The participants are 30 second-year students studying the course of BNJ21102 Occupational Safety and Health for Bachelor of Mechanical Engineering Technology (Plant) with Honours (BNL) at Universiti Tun Hussein Onn Malaysia (UTHM). This research employed a quantitative quasi-experimental design, which involved non-equivalent groups of pre-and-post-tests. The experimental group (EG) received an online platform of GBL approach, while the control group (CG) used a conventional method in T&L process. As for quantitative data collection and analysis purpose, both groups took the pre-and-post-tests of the course, and filled up a set of survey questionnaire. The result of tests revealed the EG scored higher marks than CG. Based on survey result, majority of students agree and strongly agree on the perceived usefulness and ease of use of online game based learning (OGBL) in encouraging learning. The results also discovered that the race game genre, 4-players of game, Monopoly-size of board game, and portable board game as the main preference for design specification of board game based learning (BGBL). Then, a computer aided design (CAD) software was employed to design a model of BGBL based on the preferences. Overall, the study concluded that the effective use of GBL could contribute positive motivation and encouragement of learning to the students. Nonetheless, several recommendations are highlighted for further development and improvement of the research, including the real play-testing of the game with a combination of OGBL and BGBL towards increasing the overall learning of students.